2017
DOI: 10.1097/mco.0000000000000412
|View full text |Cite
|
Sign up to set email alerts
|

Fat-soluble micronutrients and metabolic syndrome

Abstract: Purpose of reviewMetabolic syndrome (MetS) is associated with increased risk of obesity, type 2 diabetes mellitus and cardiovascular diseases. MetS prevalence has been associated with diet inadequacy. Conversely, the cumulative incidence of MetS has been inversely associated with a Mediterranean-style diet that includes many different health-beneficial nutrients. Adherence to a Mediterranean-style diet could reduce or at least stabilize metabolic risk factors.Recent findingsLow serum level of fat-soluble micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 30 publications
0
26
0
2
Order By: Relevance
“…In a randomized clinical trial with MetS patients, vitamin E was seen to exert beneficial effects on cytokines and the lipid profile [ 175 ]. Moreover, different studies have found that vitamin E could ameliorate the pathologic conditions associated with MetS such as hyperglycemia or obesity, although more studies in patients are needed to prove the consistency of these findings [ 175 , 176 ].…”
Section: Nutrients (Well-being Through Feeding)mentioning
confidence: 99%
“…In a randomized clinical trial with MetS patients, vitamin E was seen to exert beneficial effects on cytokines and the lipid profile [ 175 ]. Moreover, different studies have found that vitamin E could ameliorate the pathologic conditions associated with MetS such as hyperglycemia or obesity, although more studies in patients are needed to prove the consistency of these findings [ 175 , 176 ].…”
Section: Nutrients (Well-being Through Feeding)mentioning
confidence: 99%
“…It is common knowledge that diets rich in fruits and vegetables are associated with improved health and longevity and, since carotenoids are abundant in plants, many studies correlated the presence of these pigments with a healthy status in people (recently reviewed in [110,111,112]). Nevertheless, these observations could be merely associations based on the chemical properties of carotenoids, i.e., carotenoids are decreased in obesity because these compounds accumulate in the adipose tissue as this tissue works as a “trap” for lipophilic molecules.…”
Section: β-Carotene and Obesity; Key Findings And Technical Limitamentioning
confidence: 99%
“…They are also associated with a reduced ability to incorporate lipophilic compounds into cells, since VE is highly hydrophobic, and cannot adequately access inside cells to carry out its functions, including antioxidant activity. In this scenario, obese people are especially vulnerable to suffering dyslipidemia and chronic low-grade inflammation [129], and the presence of apolipoprotein risk variants would impair taking advantage of the properties of vitamin E, even when following current dietary recommendations.…”
Section: Influence Of Genetic Variants On Transport Management Amentioning
confidence: 99%